Perancangan Sistem Informasi Penerimaan Siswa Baru Berbasis Web Di SMK Negeri 1 Ujungbatu Kabupaten Rokan Hulu-Provinsi Riau - Fiki Sanora; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
SMK Negeri 1 Ujungbatu is one of the school that located in Rokan Hulu Regency. The school’s number of registrations increased each year. To help student candidate to apply and the selection committees to manage registration data, an information system named Sistem Informasi Penerimaan Siswa Baru Berbasis Web di SMK Negeri 1 Ujungbatu, Kabupaten Rokan Hulu-Provinsi Riau. Programming language that used for this information system are PHP Hypertext Preprocessor (PHP), Hypertext Markup Language (HTML), JavaScript, Cascading Style Sheet (CSS), My Structured Query Language (MySQL). The method that used in this information system is Waterfall. Waterfall is a systematic and sequential developing model that link one phase to another in sequence. This research produced an app that could provide ease in obtaining information and registering so that the new students admission process became more effective and efficient.Keywords: Information System, New Student Admission, Waterfall Method.